A review on An artificial neural network based on genetic algorithm for prediction of structural response of multistoried r.c.c. Structure under earthquake excitation - Rakesh Kumar, Shital.A. Patage, Abhay.B. Shelar, Krantikumar V. Mhetre (Mathematical Statistician and Engineering Applications, 2022)
— Reinforced concrete structures exhibit complexities in their structural behavior Under the Earthquake excitation due to the composite nature of the material and the magnitude of earthquake and variety of factors that affect such behavior. As such, current methods for the design and analysis of reinforced concrete slabs are limited in scope and are approximate at best as they must rely on the results of experimental tests, which are both costly and time consuming to perform. The research embodied by this title investigates the use of a branch of artificial neural network (ANN) based on genetic algorithm known as Neural Networks (NN) as a quick and reliable alternative to such experimental testing. Multistoried R.C.C. structures are the need of the society in this modern era of 21stcentury due to the limited availability of land. These multistoried R.C.C. structures are widely used for different purposes like residential, commercial, industrial, etc. Earthquake is most common natural calamity which causes the impact on the stability of R.C.C. structure. Artificial Neural Networks (ANN) based on genetic algorithms a preliminary alternative to mathematical modeling or experimental testing for quick prediction of the structural response of multistoried reinforced concrete structures. Such predictions could be used by a structural engineer on a preliminary basis to decide the initial suitability of a particular structure. Once this suitability was determined the engineer could then proceed with further, more traditional methods of design. I’ve found number of literatures which focused on applications of ANN in RCC structure design, applications of genetic algorithm on response of RCC structure. One of the literature “A NEURAL NETWORK APPROACH FOR PREDICTING THE STRUCTURAL BEHAVIOR OF CONCRETE SLABS” by Susan Hentschel in 1998, but it was limited to RCC slabs only. My research is focusing overall structural response of RCC structure under Earthquake Excitation